1994
DOI: 10.1109/50.293966
|View full text |Cite
|
Sign up to set email alerts
|

Equivalent circuit theory of spontaneous emission power in semiconductor laser optical amplifiers

Abstract: Absfruct-An equivalent circuit model for a semiconductor laser amplifier (SLA) has been developed. This model can be used with a transfer matrix method (TMM) to analyze the performance of a SLA. The validity of the model is explored in this paper by analyzing the spontaneous emission noise power in a Fabry-Perot SLA with a uniform distribution of material gain coefficient. The result is found to be identical with that derived by the Green function approach. The physical reasons for the validity of the equivale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 22 publications
1
10
0
1
Order By: Relevance
“…The circle keys and the solid curve represent, respectively, our simulations and the results of Eq. (12), and the results of the both methods are agreeable. In Fig.…”
Section: Static and Dynamic Analysis Of Laser Diodesupporting
confidence: 61%
See 1 more Smart Citation
“…The circle keys and the solid curve represent, respectively, our simulations and the results of Eq. (12), and the results of the both methods are agreeable. In Fig.…”
Section: Static and Dynamic Analysis Of Laser Diodesupporting
confidence: 61%
“…A circuit simulator also allows integration with electrical components (package parasitic, laser driver circuit, etc.). Equivalent circuit models have been separately reported for LDs [9][10][11] and SOAs [12][13][14]. However, the principles of SOAs and LDs are extremely similar.…”
Section: Introductionmentioning
confidence: 96%
“…This type of amplifier can indeed be modelled very easily by a rectangular dielectric waveguide [50]. However, modern SLAs involve more complex structures like ridge or rib waveguides [4]. In these cases, the analyses of the transverse modal fields are indeed more complicated than that outlined in in Fig.…”
Section: Analysis Of Longitudinal Travelling Fields In Slas Using Tramentioning
confidence: 99%
“…Two different approaches to analysing SLAs will then be reviewed, where their merits and shortcomings will be discussed. A third approach proposed by the authors [4] is reported next, which is based on the transfer matrix method (TMM) [5]. Using this approach, a more robust and efficient technique can be used to analyse SLAs with both relatively simple (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The active layer of an SOA has a positive medium gain but not large enough for laser emission. Equivalent circuit models have been separately reported for LDs (Lu et al, 1995;Rossi et al, 1998;Tsou & Pulfrey, 1997) and SOAs Chu & Ghafouri-Shiraz, 1994;Sharaiha & Guegan, 2000). However, the principles of SOAs and LDs are extremely similar.…”
Section: Unified Circuit Model For Semiconductor Optical Amplifiers Amentioning
confidence: 99%